IMPROVING THE CONSOLIDATED FINANCIAL REPORTING AND AUDIT METHODOLOGY (American Journal of Business Management, Economics and Banking, 2025)
In the process of presenting a consolidated financial report prepared in accordance with international standards, conclusions and recommendations are developed on the problems and their solutions that have arisen in the process of conducting an audit, improving the audit quality control system.